2019
DOI: 10.1029/2018jc014228
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Propagation of M2 Internal Tides Modulated by the Kuroshio Northeast of Taiwan

Abstract: The variability and energetics of M2 internal tides during their generation and propagation through the Kuroshio flows northeast of Taiwan are investigated using a high‐resolution numerical model. The corrugated continental slopes, particularly the I‐Lan Ridge and Mien‐Hua Canyon, are first identified as the energetic sources of M2 internal tides. The domain‐integrated M2 barotropic‐to‐baroclinic conversion rate under the Kuroshio influence is ~2.35 GW, ~0.9 GW of which is generated at the I‐Lan Ridge, ~0.93 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 89 publications
0
22
0
Order By: Relevance
“…The dominant coherent semidiurnal ITs suggested that in November, the ITs remained phaselocked with the local barotropic tides, and they were generated in the vicinity of the observation site. The Mien-Hua Canyon and North Mien-Hua Canyon are the closest significant generation sites of semidiurnal ITs [23,25,27], and they are the probable generation sites of the observed semidiurnal ITs. Vertical modes of the semidiurnal internal tides in October and November are shown in Figure 7.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The dominant coherent semidiurnal ITs suggested that in November, the ITs remained phaselocked with the local barotropic tides, and they were generated in the vicinity of the observation site. The Mien-Hua Canyon and North Mien-Hua Canyon are the closest significant generation sites of semidiurnal ITs [23,25,27], and they are the probable generation sites of the observed semidiurnal ITs. Vertical modes of the semidiurnal internal tides in October and November are shown in Figure 7.…”
Section: Resultsmentioning
confidence: 97%
“…The East China Sea (ECS) have a wide continental shelf and a deep trough (the Okinawa Trough) connected by a steep continental slope. The generation of ITs in the ECS has been reported based on observations [19][20][21][22][23][24] and numerical models [25][26][27]. Lien et al found that on the continental slope to the northeast of Taiwan Island, the semidiurnal internal tidal energy flux exhibits strong temporal and spatial variations, and it has a seaward direction [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the internal tide passes through a mesoscale eddy, the energy of the mode 1 internal tide can be refracted and transmitted to higher-mode waves (e.g., Farrari and Wunsch, 2008;Henning and Vallis, 2005). The eddy flows can also directly increase vertical shear and, subsequently, the internal tide energy dissipation rate (e.g., Chavanne et al, 2010;Dunphy and Lamb, 2014). The anticyclones induce higher tidal mix-ing than cyclones, probably because of the chimney effects associated with distinct vorticities (Jing et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the CTRL magnitudes were similar to those of TPXO7.2 and both decreased from west to east in both Figures 3a and 3b. Small-scale variations of the cophase lines near the ridges in Figure 3a reflect the impact of the M 2 baroclinic tides (Chang et al, 2019;Niwa & Hibiya, 2004). To provide a quantitative assessment of the modeled barotropic tides, the absolute root-mean-square error (RMSE) was calculated following Cummins and Oey (1997),…”
Section: Model Verificationmentioning
confidence: 99%